Mathematical modelling and simulation of hydrotropic delignification - Indah Hartati; Wahyudi Budi Sediawan; Hary Sulistyo; Muhammad Mufti Azis; Moh Fahrurrozi (Jurnal Rekayasa Proses, 2019)
Delignification is a fundamental step in bio-refinery for lignocellulose feedstock processing. Hydrotropic delignification is considered as a promising alternative compared to other conventional delignification processes due to the use of mild chemicals. In this paper, a quantitative description of hydrotropic delignification for a cylindrical biomass particle is presented by using fundamental concepts of chemical kinetics and transport processes. The development of hydrotropic delignification model was based on following assumptions: i) lignin in the biomass is immobile, ii) delignification is considered as a simultaneous process which involves intra-particle diffusion of hydrotropic agent followed by second order reaction for lignin and hydrotropic chemical, as well as intra-particle product diffusion. Finite difference approximation was applied to solve the resulting partial and ordinary differential equations. The simulation results of the proposed model may describe the concentration profiles of lignin, hydrotropic agent and soluble product distributions in a cylindrical solid particle as a function of radial position and time. In addition, the model could also predict the concentration of hydrotropic agent and soluble product in the liquid phase as well as the yield and conversion as a function of time. A local sensitivity analysis method using one factor at a time (OFAT), has been applied to investigate the influence of particle size and hydrotropic agent concentration to the yield and conversion of the hydrotropic delignification model. Validation of the proposed model was conducted by comparing the numerical results with an analytical solution for a simple case diffusion in cylinder with constant surface concentration and in the absence of chemical reaction. The validation result showed that the hydrotropic delignification model was in good agreement with the analytical solution.